Nonlinear optical materials - Thompson, Peter Anthony (Cranfield University, 1994)
Twenty different materials have been successfully deposited as Langmuir- Blodgett monolayer films. All exhibit second harmonic generation (SHG) when irradiated with laser light at 1064 nm. E-1-docosyl-4-{2-(4-dimethylami nophenyl)ethenyl}quinolinium bromide (C22H45QHBr) and E-1-docosyl-4-{2-(4-dimethy laminonaphthyl)ethenyl}quinolinium bromide (C22H45QNBr) have been deposited separately as multilayer films. They form Y-type structures when deposition is alternated with the material N-docosyl-4- methylquinolinium bromide. The nonlinear responses are quadratic up to 20 and 10 bilayers respectively and the response from the thick films is only 2 orders less than that produced by a Y-cut quartz plate. Similar results were obtained with C22H45QHBr when interleaved with 4,4'-dioctadecyl-3,5,3', 5'- tetra me thyldipyrrylmethenehydrobromide. Ellipsometry studies of the 10 bilayer film of C H45QNBr indicate that the structure is interdigitated. This explains the stability of the film which gave the same SH response up to 6 months after deposition. A 10 bilayer films has also been fabricated using E-1- docosyl-4-{2-(4-{2-(4-dimethylaminophenyl)ethenyl}benzyl)ethenyl}pyridinium bromide (C22H45PBHBr) alternated with E-1-docosy1-4-{2-(4-methylphenyl)ethenyl}pyridinium bromide (C22H45PT). E-1-octadecyl-4-{2-(4-methyloxyphenyl)ethenyl}pyridinium iodide and E-1- methyl-4-{2-(4-octadecyloxyphenyl)ethenyl}pyridinium iodide have been fabricated into monolayer films that are transparent at 1064 and 532 nm, therefore resonant enhancement does not contribute to their nonlinear response which is attributed solely to charge transfer in the molecule. Mixed solutions of E-1-octadecyl-4-{2-(4-methyloxyphenyl)ethenyl}pyridinium iodide and sodium octadecylsulphate (C1SH37OSO3 Na+) have been deposited as very stable monolayers. The nonlinear response from the mixed film offers a significant improvement upon the performance of the film containing pure hemicyanine. Novel zwitterionic materials have been fabricated as LB monolayers that also exhibit SHG.